2022
DOI: 10.1186/s12931-022-02001-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation for clinical benefit of metformin in patients with idiopathic pulmonary fibrosis and type 2 diabetes mellitus: a national claims-based cohort analysis

Abstract: Background Idiopathic pulmonary fibrosis (IPF) is a chronic progressive lung disease with high morbidity and limited treatment options. Type 2 diabetes mellitus (T2DM) is a common comorbid illness among patients with IPF and is often treated with metformin, the first-line agent in the management of T2DM. There is growing evidence demonstrating metformin’s anti-fibrotic properties; however, there is little real-world clinical data regarding its potential effectiveness in IPF. This study aims to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 63 publications
0
22
0
Order By: Relevance
“…However, both studies were limited by their small sample sizes ( n = 28 and n = 71). In contrast, a recent retrospective cohort study that included 3,599 patients with IPF and T2DM showed a significant 54% reduction in all-cause mortality with MET treatment ( Teague et al, 2022 ). This effect was substantially better than that of the current anti-fibrotic agents (23%) ( Dempsey et al, 2019 ).…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…However, both studies were limited by their small sample sizes ( n = 28 and n = 71). In contrast, a recent retrospective cohort study that included 3,599 patients with IPF and T2DM showed a significant 54% reduction in all-cause mortality with MET treatment ( Teague et al, 2022 ). This effect was substantially better than that of the current anti-fibrotic agents (23%) ( Dempsey et al, 2019 ).…”
Section: Discussionmentioning
confidence: 95%
“…However, it is worth noting that this study observed the effect of MET in patients with PF and T2DM, and there is insufficient evidence of a direct causal relationship between MET and PF. In addition to its anti-fibrotic effect, MET also has cardioprotective and hypoglycemic effects ( Holman et al, 2008 ; Roumie et al, 2012 ), which may be responsible for reducing mortality in patients with PF and T2DM ( Teague et al, 2022 ). Therefore, further clinical trials are required.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, and in spite of all advances in our comprehension of idiopathic pulmonary fibrosis, current therapeutic options still have great limitations [ 121 , 122 , 123 ]. Therefore, the search, analysis, and discussion of new treatment options are necessary.…”
Section: Non-smad-dependent Signaling Pathways In Emt Induced By Tgfβmentioning
confidence: 99%